-9x + 2 > 18.
-9x > 16
x < -16/9
13x ≤ -19
x ≤ -19/13
x < -16/9 or. x ≤ -19/13
Answer:
1.4
Step-by-step explanation:
x^2*(-3x)=-3x^3. The power of x becomes 3 because you add the powers of x. (2+1=3)
Answer:
Approximately 6.4
Step-by-step explanation:
We can use the pythagorean thereom here, that tells us (a^2)+(b^2)=c^2. C is the hypotenuse, the side opposite from the right angle, while a and b are the other sides. We can insert 5 and 4 as a and b, and solve for c
:(5^2)+(4^2)=c^2
:25+16=c^2
:41=c^2
:sqrt(41)=6.4=c (We square rooted both sides. 6.4 is only rounded to the nearest hundredths place.) Hope this helps!